Joint university-industry laboratories through the lens of proximity dimensions: moving beyond geographical proximity - Mahdad, M.; Minh, Thai Thi; Bogers, M. L. A. M.; Piccaluga, A. (Emerald Publishing Limited, 2020)
Purpose – There is little known about investigating the importance of all proximity dimensions simultaneously as a result of geographical proximity on university-industry collaborative innovation. This paper aims to answer the question of how geographically proximate university and industry influence cognitive, social, organizational, institutional and cultural proximity within university-industry joint laboratories and finally, what is the outcome of these interplays on collaborative innovation.